Achieving high ductility in a selectively laser melted commercial pure-titanium via in-situ grain refinement. (15th January 2021) - Zhang, Jingqi; Liu, Yingang; Bayat, Mohamad; Tan, Qiyang; Yin, Yu; Fan, Zhiqi; Liu, Shiyang; Hattel, Jesper Henri; Dargusch, Matthew; Zhang, Ming-Xing
Abstract: Grain refinement of additively manufactured titanium and titanium alloys can be promoted via adding foreign elements or particles, but it may lead to a reduction in ductility due to the formation of brittle intermetallic compounds. The present study shows that in-situ grain refinement of commercially pure titanium (CP-Ti) can be achieved through properly controlling the selective laser melting (SLM) parameters. It was found that higher input energy density worked in favour of grain refinement. Detailed microstructural characterization coupled with multi-physics simulation were performed to reveal the grain refinement mechanism. This was attributed to the intrinsic heat treatment (IHT) effect which resulted from the cyclic reheating inherent to the SLM process. As a result, the refined CP-Ti exhibited an exceptionally high ductility of 34.3 ± 0.5% without notable mechanical anisotropy. This work demonstrates the feasibility of utilizing thermal cycling of additive manufacturing (AM) to refine grains of metals without changing the composition. Graphical abstract: Image, graphical abstract